Equity research: LindtT & Sprungli: premium chocolate - Olivucci, Gian Pietro (2021)
By implementing a DCF model, we estimated Lindt & Sprüngli market value of share price, incorporating our belief about the future landscape of the business and economy. The work aims at delivering to investors a final strategical recommendation, based on our estimation and actual stock price of the company.